Creating a positive team climate 20 practical ideas - Parker, Glenn M. 1938- (HRD Press, 2009)
In Volume IV of the Parker Team Series, Creating a Positive Team Climate: 20 Practical Ideas author Glenn Parker shows how to evaluate an rehabilitate your team for outstanding results. This easy to read manual is chock full of practical advice, not theory; use it from the moment you open it up!
Keywords: Teams in the workplace -- Management; Employee motivation; Personnel management; Personnel Management; Équipes de travail; Gestion; Personnel; Motivation; Personnel; Direction; BUSINESS & ECONOMICS; Workplace Culture; BUSINESS & ECONOMICS; Corporate Governance; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Organizational Development; Teams in the workplace; Management